THE ANTECEDENTS OF INTENTION FOR ECOTOURISM - Salma, Iman; Ayu Ekasari (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2024)
This research aims to examine the impact or consequences of environmental attitudes and identity. Therefore, the authors of the framework describe the relationship between environmental attitudes, ecotourism identity, hedonism in ecotourism, and ecotourism intentions. An online survey on Google Form was conducted with a sample of 135 individuals who knew the ecotourism destinations of Ujung Kulon National Park and Komodo National Park. The results show that environmental attitudes directly influence tourists to direct ecotourism destinations. Apart from that, tourist identity is also a factor that encourages tourists to visit. However, hedonism in ecotourism has no effect on the intensity of visiting ecotourism destinations. The results of this research can be useful for ecotourism destination managers to design appropriate promotional strategies.